Authenticity of Auction Minutes as a Basis for Transfer of Land and or Building Sale-Purchase Rights - Muljono, Bambang Eko; Sastradinata, Dhevi Nayasari; Abidin, Zaenal (Universitas Islam Lamongan, 2025)
ABSTRACT This research is motivated by the Authenticity of Auction Minutes as the Basis for the Transfer of Land and/or Building Sale and Purchase Rights. to find the legal basis and explain the proof of auction minutes with applicable legal provisions. This research uses a normative legal research type, using a statutory approach and a conceptual approach. The legal materials in this study are primary legal materials and secondary legal materials. The results of this study can be concluded that the Authenticity of Auction Minutes as the Basis for the Transfer of Land and/or Building Sale and Purchase Rights is very important; auction minutes serve as evidence that the relevant auction legal act has been carried out. The legal act is cash in nature, as well as providing the transfer of rights to the object in question to the recipient of the rights. The form of the legal basis for Article 1, number 34 of the Regulation of the Minister of Finance Number 122 of 2023 concerning Auction Implementation Guidelines. And regulated in the provisions of Article 35 Vendu Reglement (Auction Regulations) concerning the Regulation of Public Sales in Indonesia (Ordinance of February 28, S. 1908-189 in effect since April 1, 1908). The provisions in Article 1868 of the Civil Code stipulate that: